Career Pathways and Professional Outcomes of BEED Graduates: A Tracer Study at Negros Oriental State University – Siaton Campus - Caluscusin, Michael Mark; Bajas-Caluscusin, Anna Maneleine; Alido, Rochelle Ann; Enojo, Marc Del; Gadingan, Nicka Chenkie; Gadingan, Gwyneth; Raip, John; Kirit, Karen Joy; Caluscusin, David Emmanuel Noel (Journal of Interdisciplinary Perspectives, 2025)
This comprehensive tracer study investigates the professional trajectories and outcomes of Bachelor of Elementary Education (BEED) graduates of Negros Oriental State University (NORSU) Siaton Campus, focusing on employment, educational adequacy, skill relevance, and broader personal and professional impacts. Utilizing a convenience sampling technique, the study surveyed 685 graduates through online platforms and social media to assess their employment status, educational contributions to personal and professional growth, and further education pursuits. Data were subjected to descriptive statistical analysis. The findings indicate that over half of both female and male graduates are married, with nearly half being single. A significant majority of graduates hold bachelor's degrees, with 88.3% not pursuing further studies. Employment data revealed diverse organizational affiliations, with 68% of graduates working in jobs related to their college courses, and nearly half in their first job post-graduation. Moreover, most graduates work in the Philippines, earning between 10,000 and 40,000 pesos monthly. Graduates rated the contribution of their education highly, noting significant personal and professional growth, although some pointed out areas for improvement, like library and laboratory resources. The study stressed NORSU’s programs in preparing graduates for the 21st-century workforce, emphasizing positive employment outcomes and professional recognition.